PENGARUH LAMA PEMBERIAN DIET ATEROGENIK TERHADAP INDEKS ATEROGENIK SERUM Rattus novergicus STRAIN WISTAR JANTAN - Ariza Julia Paulina; Enikarmila Asni; Mardhiah Gaffar (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Atherosclerosis is defined as a chronic inflammation which is marked by the accumulation of cholesterol and ester cholesterol in the sub endotelial vascular tissue. The ratio of LDL/HDL (atherogenic index) is the main parameter in atherosclerosis and CHD incidence. The purpose of this research is to know the effect of long giving atherogenic diet against serum atherogenic index in male Wistar rat. This study was an experimental research with the post test-only control group design, by using male rats (Rattus novergicus) of 2-3 month with the average weight range of 160-240 gr. The rats are then divided into 4 group which are: control group given with standard diet, the 5 weeks atherogenic diet group, the 8 weeks atherogenic group, and the 12 weeks atherogenic group, in which group consist of 6 rats. The atherogenic diet (2% cholesterol, 5% goat’s fat, and 0,2% cholic acid) is given ad libitum as much as 20 gr/ea/day. The result are then analyzed with the one way ANOVA method, showing that there’s a adequate difference (p=0,000). As for the Post Hoc Test (p=0,000), the result show is that the atherogenic diet does increase the atherogenic index of the rats blood serum. And as for the Spearman test (0,969), it show is a significant positive correlation between the atherogenic index and the given duration of the atherogenic diet. In this research we can conclude that the longer given atherogenic duration, the higher the atherogenic index will become on male Wistar rats (Rattus novergicus).Keywords: Atherosclerosis, atherogenic diet, atherogenic index, LDL/HDL ratio, rats (Rattus novergicus)